Response of photosynthesis to light and CO2 concentration in spring wheat under progressive drought stress - Fei Chen; Kai Zhang; Shuang Yan; Runyuan Wang; Heling Wang; Hong Zhao; Funian Zhao; Yue Qi; Yang Yang; Xingxing Wei; Yurui Tang (BMC Plant Biology)
Abstract Background Global climate change significantly affects photosynthesis in spring wheat. However, the successive dynamic effects of multiple environmental interactions on photosynthesis in spring wheat have been inadequately investigated. This study conducted pot control experiments to determine photosynthesis characteristics, namely light and CO2 response curves, in spring wheat under progressive drought stress. Results Progressive drought stress caused all parameters of the light response curve to decrease logistically and all parameters of the CO2 response curve to change exponentially. There were noticeable thresholds for these parameter changes. The ability of spring wheat to utilize light was weakened by progressive drought stress. Under all drought levels, the reduction in photosynthetic capacity was greater under strong light than under weak light. The effects on CO2 utilization and the corresponding photosynthetic capacity depended on the drought level and CO2 concentration. The optimal light intensity (Iopt) for spring wheat showed a logistic decreasing trend under progressive drought stress. Unexpectedly, the optimal atmospheric CO2 concentration (CO2opt) remained at 800 µmol·mol− 1 under drought stress, which was less severe than extreme drought. Conclusions Our results showed that progressive drought stress, combined with different environmental factors, had distinct impacts on the photosynthetic efficiency and carbon assimilation capacity of spring wheat, providing a basis for rational carbon and water resource utilization in spring wheat under climate change.